Folktale Text Transformation: Learning Model to Read Appreciatively - Titin Setiartin; Jojo Nuryanto; Ipah Muzdalipah (STKIP Singkawang, 2017)
This study focused on the development of learning models to read appreciatively through folktale text transformation. This study was conducted as an effort to improve the reading skills appreciatively of 12th-grade students in vocational schools. This study was a mixed method research with the subsequential design. Data were analysed by qualitative and quantitative techniques with a matching pattern of test-pretest post-test. The results showing the difference values between Randomized Pretest and Posttest significantly. Based on this differences, can be inferred that the developed learning model of narrative text transformation was capable of substantially improving skills of reading appreciatively of 12th-grade students in vocational schools. Thus, learning models to read appreciatively through folktale text transformation was effective and fit to be used in improving skills of reading appreciatively